Teachers' understandings of the 2011 PRC curriculum for teaching English - Lei, Man (2016)
This thesis reports an enquiry into Chinese primary and junior high school English teachers’ perceptions of, and responses to The Revised Curriculum (2011) for Full-time Compulsory Education. This document claims to hold a very different view of English teaching from pervious curricula, but this claim is largely unexplored.